2020
DOI: 10.1681/asn.2020050615
|View full text |Cite
|
Sign up to set email alerts
|

AKI in Hospitalized Patients with COVID-19

Abstract: Background Early reports indicate that AKI is common among patients with coronavirus disease 2019 (COVID-19) and associated with worse outcomes. However, AKI among hospitalized patients with COVID-19 in the United States is not well described. Methods This retrospective, observational study involved a review of data from electronic health records of patients aged $18 years with laboratory-confirmed COVID-19 admitted to the Mount Sinai Health System from February 27 to May 30, 2020. We describe the frequency of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

69
697
14
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(815 citation statements)
references
References 22 publications
69
697
14
35
Order By: Relevance
“…In a recent meta-analysis, it was found that 52% of patients who developed AKI died [13]. Another study showed that, chronic kidney disease and male sex were independent predictors of AKI severity [14]. However, as seen in our cohort, consequences of all AKIs in COVID-19 are not the same.…”
Section: Discussioncontrasting
confidence: 61%
“…In a recent meta-analysis, it was found that 52% of patients who developed AKI died [13]. Another study showed that, chronic kidney disease and male sex were independent predictors of AKI severity [14]. However, as seen in our cohort, consequences of all AKIs in COVID-19 are not the same.…”
Section: Discussioncontrasting
confidence: 61%
“…While the reported incidence of AKI among hospitalized patients with COVID-19 varies widely, recent studies from the US have suggested an incidence as high as 37-40%. [1][2][3] AKI among hospitalized patients is associated with poor prognosis, 4 increased length of stay, and increased health care costs. 5 Patients who survive AKI appear to be at an increased risk for death and incident chronic kidney disease (CKD).…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…(9-11) A recent systematic review and meta-analysis of 22 observational studies from China and the United States reported on renal complications in 17,391 hospitalized patients with COVID-19. The pooled incidence for AKI (n = 22 studies) was 11.0% (7.4-15.1) with 6.8% (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) requiring kidney replacement therapy [KRT]. Although AKI was the common outcome reported by studies; hyperkalaemia was the most frequent renal complication with an incidence of 12.5%.…”
Section: Introductionmentioning
confidence: 99%
“…(4) The prevalence of AKI resulting in the need for KRT ranges from 0.8% in China to 20% of hospitalized patients in New York. (12,13) In a large New York cohort AKI was commonly seen in association with respiratory failure and mechanical ventilation. (10) Patients developing AKI in the setting of COVID-19 have poor outcomes, irrespective of their age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation